Cancer specific mortality in patients with collecting duct vs. clear cell renal carcinoma. (February 2023) - Panunzio, Andrea; Sorce, Gabriele; Tappero, Stefano; Hohenhorst, Lukas; Garcia, Cristina Cano; Piccinelli, Mattia; Tian, Zhe; Tafuri, Alessandro; De Cobelli, Ottavio; Chun, Felix K.H.; Tilki, Derya; Terrone, Carlo; et al.
Abstract: Background: Collecting duct carcinoma (CDC) is biologically more aggressive than clear cell renal cell carcinoma (ccRCC). We tested for differences in cancer specific mortality (CSM) rates according to CDC vs. ISUP (International Society of Urological Pathology) 4 ccRCC histological subtype. We hypothesized that the survival disadvantage still applies, even after most detailed adjustments. Methods: Within Surveillance, Epidemiology, and End Results database (2004–2018), we identified 380 CDC vs. 6273 ISUP 4 ccRCC patients of all stages. Propensity score matching (age, sex, race/ethnicity, T, N, and M stages, nephrectomy, and systemic therapy status), Kaplan-Meier plots and multivariable Cox regression models were used. Results: All 380 CDC were matched (1:2) with 760 ISUP4 ccRCC patients. Prior to matching CDC patients exhibited higher rates of lymph node invasion (37.6 % vs. 14.7 %, p  < 0.001), and of distant metastases (40.8 % vs. 30.4 %, p  < 0.001). Systemic therapy rates were higher in CDC (29.5 % vs. 20.5 %, p  < 0.001). However, nephrectomy rates were higher in ISUP4 ccRCC patients (97.5 % vs. 84.7 %, p  < 0.001). After matching, in multivariable Cox regression models addressing CSM, CDC was associated with a HR of 1.5 ( p  < 0.001) in the overall population vs. 1.9 ( p  = 0.014) in stage I-II vs. 1.4 ( p  = 0.022) in stage III vs. 1.6 in stage IV ( p  < 0.001), relative to ISUP4 ccRCC. Conclusion: CDC patients exhibited 40–90 % higher CSM than their ISUP4 ccRCC counterparts in the overall analysis, as well as in stage specific analyses. The CSM disadvantage applies despite higher rates of systemic therapy in CDC patients. Highlights: Collecting duct carcinoma is stated as a high-grade tumor by ISUP. The present study firstly compared collecting duct and ISUP 4 clear cell renal carcinoma. Collecting duct carcinoma exhibited 40–90 % higher mortality according to stage. The survival disadvantage applies even with the strictest available statistical methodology.